The Digital Barbershop: Blogs and Online Oral Culture Within the African American Community. (December 2016) - Steele, Catherine Knight
For African Americans, the legacy of oral communication within the community is being transferred to online spaces. Blogging provides a platform with features that mirror many of the components of the Black barbershop. The barber and beauty shop symbolize a space of retreat, wherein African Americans have formed alternate publics used to critique the dominant culture, foster resistance, and strengthen African American institutions. Analysis of nine African American–authored blogs using a method of critical technocultural discourse analysis demonstrates that each blog used traditional Black rhetorical strategies while making modifications to contemporary goals. The strategies involve modifications made to traditional Black humor and folktales. The writing style is highly performative, yet relies upon participant interaction. This reliance on orality is a necessary force in the maintenance of cultural traditions that have long worked to assist in group definition and acts of resistance in political power struggles. By utilizing modified song, narrative, and fables to articulate resistance and craft African American identity, African American online oral culture persists as a strategy to house political discourse within the often hidden enclave spaces of the digital barbershop.